HAPPINESS AT WORK: A SYSTEMATIC LITERATURE REVIEW OF STUDIES PUBLISHED IN THE PERIOD 2022–2025 - Jadrić, Ivana (Economic Review: Journal of Economics and Business, 2025)
This study provides a comprehensive review of research on happiness at work – a dynamic and attractive concept that is constantly evolving. Given the dynamic nature of the concept and the impact of various factors on its understanding, the analysis is focused on scientific papers published in the last three years, with the aim of identifying the latest research trends. In order to map research tendencies and identify existing research gaps, 2,046 scientific articles retrieved from the Web of Science and Scopus databases were analyzed, using the key word happiness at work. After applying the PRISMA method and eliminating the papers that did not fully correspond to the topic, the final analysis included 98 relevant articles that were completely in the scope of the research. The research results indicate a growing interest in this topic, which is reflected in the growing number of publications in the last period. In addition, a strong connection of happiness at work with the concepts of corporate social responsibility, sustainability, management styles, and the formation of a positive organizational climate was observed. Also, there is a trend of increased publication of papers on this topic in specific sectors such as healthcare, banking, and education.